N-Heterocyclic carbene-catalyzed diastereoselective synthesis of β-lactone-fused cyclopentanes using homoenolate annulation reaction - Mukherjee, Subrata; Mondal, Santigopal; Patra, Atanu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
NHC-catalyzed annulation of enals with 2-enoylpyridines or 2-enoylpyridine N-oxides leading to the diastereoselective synthesis of β-lactone-fused cyclopentanes is reported. The reaction proceeds via the generation of homoenolate equivalent intermediates and tolerates a broad range of functional groups.